2018
DOI: 10.21111/sjic.v1i2.2851
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Komunikasi Dakwah dalam Pembinaan Mental Narapidana

Abstract: Banyaknya residivis yang kembali melakukan kejahatan setelah keluar dari penjara menjadi masalah yang meresahkan masyarakat. Masalah ini merupakan pekerjaan rumah bagi lembaga pemasyarakatan dalam membina anak didiknya yaitu para Warga Binaan Pemasyarakatan (WBP) sehingga perlu diterapkan strategi komunikasi dakwah yang tepat dan kreatif. Tujuan penelitian ini untuk mengetahui strategi komunikasi dakwah yang dilakukan Lembaga Pemasyarakatan di kota Metro, serta faktor pendukung dan penghambat dalam kegiatan da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Research related to da'wah strategies has been widely carried out in several prisons, such as research the title of mental development in correctional institutions: a review of da'wah communication strategies (Ariyanto et al, 2019) from this study concluded that the three most effective da'wah strategies carried out to inmates so that it has a positive impact on the inmates. The three strategies carried out are; 1) the strategy of recitation (reading the verses of Allah); 2) tazkiyah strategy, which means selfpurification.…”
Section: Introductionmentioning
confidence: 78%
“…Research related to da'wah strategies has been widely carried out in several prisons, such as research the title of mental development in correctional institutions: a review of da'wah communication strategies (Ariyanto et al, 2019) from this study concluded that the three most effective da'wah strategies carried out to inmates so that it has a positive impact on the inmates. The three strategies carried out are; 1) the strategy of recitation (reading the verses of Allah); 2) tazkiyah strategy, which means selfpurification.…”
Section: Introductionmentioning
confidence: 78%
“…(Emqi, 2014). Ariyanto et al (2019) found that religious guidance for prisoners using the strategy of reading the Qur'an, lectures, zikr together, and ta'lim concluded that there was a change in awareness and a more positive religious attitude. The increase in the religiosity of prisoners arises when religious guidance in the form of congregational prayer, dhikr, prayer, reading the Qur'an, lectures, and studying the books in the Al-Hikmah Islamic boarding school in prison (Ikhwani et al, 2021).…”
Section: Islamic Mental Guidance For Prisoners Inmentioning
confidence: 99%
“…Perbedaannya dapat dilihat pada jenis dan sifat penelitiannya, penelitian ini menggunakan penelitian kuantitatif di mana data diperoleh dari observasi lapangan sedangkan diatas menggunakan penelitian kualitatif berdasarkan penelitian di mana data diperoleh dari observasi, dokumentasi dan wawancara. Keempat, (Budi Ariyanto, 2017) dalam skripsinya berjudul "Strategi Dakwah dalam Pembinaan Spiritual Narapidana". Persamaan penelitian di atas terlihat pada poros penelitian yang berkaitan dengan perkembangan mental bertahap.…”
unclassified